The Study of Learning Style Preferences of Undergraduate Students for Teaching Adaption - Waiprom, Nonglakshana (International Journal of Psychosocial Rehabilitation, 2020)
Knowing students preferences regarding learning style enables teachers to use more effective method of providing information and to choose better educational tools for a particular students. The purpose of this research is to address the use of David Kolb learning style to investigate the learning style preferences of undergraduate students whether there are significant differences across four dimensions of David Kolb Experiential Learning Theory due to gender, year of study, and faculty. This is to be a guideline for improving teaching method according to learning style preferences find out. Questionnaires were distributed to a sample of 398 undergraduate students at Rajamangala University of Technology Thanyaburi on Academic year of 2016. Descriptive statistics were used to present the main characteristics of correspondents and the results of the study. The results of study illustrated that gender has no impact on learning styles preference, but most of undergraduate students have the difference of learning style due to year of study, and faculty which mostly are Accommodator regarding David Kolb’s learning style which their strength is ‘doing’ and ‘risk-taking’, and good at adapting one-self to new situation.. The teaching adaptation to this research’s result is the educator should focus on involving interpersonal experience of students to the real world situations. This study has some limitations. First, the findings of the study are based on the data collected from only one university. Second, the sample is limited to Undergraduate students, therefore, there might be different learning style preferences from Graduate students. On the other hand, it has a number of implications for educator and students. The students will benefit from knowing their own learning style. Educator will also benefit from the result of this study in the sense that they need to adopt teaching style and strategies that match the learning styles of the majority of students.